Dietary supplementation and doping-related factors in high-level sailing - Rodek, J.; Sekulic, D.; Kondric, M. (Journal of the International Society of Sports Nutrition, 2012)
Although dietary supplements (DSs) in sports are considered a natural need resulting from athletes` increased physical demands, and although they are often consumed by athletes, data on DS usage in Olympic sailing are scarce. The aim of this study was to study the use of and attitudes towards DSs and doping problems in high-level competitive sailing. Methods The sample consisted of 44 high-level sailing athletes (5 of whom were female; total mean age 24.13 ± 6.67 years) and 34 coaches (1 of whom was female; total mean age 37.01 ± 11.70). An extensive, self-administered questionnaire of substance use was used, and the subjects were asked about sociodemographic data, sport-related factors, DS-related factors (i.e., usage of and knowledge about DSs, sources of information), and doping-related factors. The Kruskal-Wallis ANOVA was used to determine the differences in group characteristics, and Spearman`s rank order correlation and a logistic regression analysis were used to define the relationships between the studied variables. Results DS usage is relatively high. More than 77% of athletes consume DSs, and 38% do so on a regular basis (daily). The athletes place a high degree of trust in their coaches and/or physicians regarding DSs and doping. The most important reason for not consuming DSs is the opinion that DSs are useless and a lack of knowledge about DSs. The likelihood of doping is low, and one-third of the subjects believe that doping occurs in sailing (no significant differences between athletes and coaches). The logistic regression found crew number (i.e., single vs. double crew) to be the single significant predictor of DS usage, with a higher probability of DS consumption among single crews. Conclusion Because of the high consumption of DSs future investigations should focus on real nutritional needs in sailing sport. Also, since athletes reported that their coaches are the primary source of information about nutrition and DSs, further studies are necessary to determine the knowledge about nutrition, DSs and doping problems among athletes and their support teams (i.e., coaches, physicians, and strength and conditioning specialists).